Discussion issues of adjusting the tax base when spliting a business - Pilipenko, Aleksandr A. (Journal of the Belarusian State University. Law, 2024)
At the normative, doctrinal and applied levels the author of the article analyses the problems of determining the tax consequences of splitting a business, taking into account the actually paid amounts of mandatory payments by a real taxpayer. It is concluded that the tax reconstruction model used by the regulatory authorities does not comply with the principle of tax fairness. At the by-law level, it is necessary to clearly define the methodology for adjusting the tax base when splitting a business, taking into account the reflection of all tax obligations of a real taxpayer, including fragmented entities controlled by him.